The relationship between genetic risk variants with brain structure and function in bipolar disorder : a systematic review of genetic-neuroimaging studies - Pereira, Licia P. (2017)
Genetic-neuroimaging paradigms could provide insights regarding the pathophysiology of bipolar disorder (BD). Nevertheless, fi ndings have been inconsistent across studies. A systematic review of gene-imaging studies involving individuals with BD was conducted across electronic major databases from inception until January 9th, 2017. Forty-four studies met eligibility criteria (N = 2122 BD participants). Twenty-six gene variants were investigated across candidate gene studies and 4 studies used a genome-wide association approach. Replicated evidence (i.e. in > 2 studies) suggests that individuals with BD carrying the BDNF Val66Met risk allele could have reduced hippocampal volumes compared to non-carriers. This review underscores the potential of gene- neuroimaging paradigms to provide mechanistic insights for BD. However, this systematic review found a single replicated fi nding. Suggestions to improve the reproducibility of this emerging fi eld are provided, including the adoption of a trans-diagnostic approach.